Analysis of Public Sector Financial Performance Using Value for Money in Tangerang Regency - Denny Erica; Irwin Ananta Vidada; Ani Rakhmanita; H. Hoiriah; S. Saridawati (Manunggal Halim Jaya, 2024)
Public sector financial performance requires evaluation as a form of evaluation so that financial performance is more optimal. The financial performance of the Tangerang Regency Government in this study uses the Value for Money (VfM) approach with factors from three main factors, namely economy, efficiency, and effectiveness in 2014 to 2023. Based on the analysis of the public sector financial performance of Tangerang Regency, it is very economical with an average of 101.33% and very efficient with an average of 112.93%, but its efficiency is still low with an average of 98.54%. The results of this analysis can be used as evaluation material for the Tangerang Regency Government to carry out efficiency in public sector financial performance, so that the Tangerang Regency Government can optimize the quality of service to the local community.